2012
DOI: 10.1007/s10661-011-2512-x
|View full text |Cite
|
Sign up to set email alerts
|

Soil application of dinitroaniline and arylphenoxy propionic herbicides influences the activities of phosphate-solubilizing microorganisms in soil

Abstract: An experiment was conducted under laboratory conditions to investigate the effect of two systemic herbicides, viz. pendimethalin (a dinitroaniline) and quizalofop (an arylphenoxy propionic acid) at their recommended field application rates (1.0 kg and 50 g active ingredient per hectare, respectively), either separately or in a combination, on growth and activities of phosphate-solubilizing microorganisms in relation to their effects on biochemical transformations and availability of organic carbon, total and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 8 publications
2
5
0
Order By: Relevance
“…Application of both the herbicides, in general, significantly increased the phosphate-solubilizing capacities of soil up to 15 days of sampling, followed by a gradual decrease up to the end of the experiment. This was in accordance with the proliferation of the phosphate-solubilizing microorganisms (Ahemad and Khan, 2011;Das et al, 2012a) and was confirmed by the presence of significant positive correlation (r = 0.817, p < 0.01) between proliferation of phosphate-solubilizing microorganisms and their capacities in solubilizing insoluble phosphates in soil.…”
Section: Effect On Biochemical Processessupporting
confidence: 80%
See 1 more Smart Citation
“…Application of both the herbicides, in general, significantly increased the phosphate-solubilizing capacities of soil up to 15 days of sampling, followed by a gradual decrease up to the end of the experiment. This was in accordance with the proliferation of the phosphate-solubilizing microorganisms (Ahemad and Khan, 2011;Das et al, 2012a) and was confirmed by the presence of significant positive correlation (r = 0.817, p < 0.01) between proliferation of phosphate-solubilizing microorganisms and their capacities in solubilizing insoluble phosphates in soil.…”
Section: Effect On Biochemical Processessupporting
confidence: 80%
“…Sustaining the earlier reports (Jones and Oburger, 2011;Das et al, 2012a), stimulation of phosphate-solubilizing microorganisms manifested greater solubilization of insoluble phosphates in soil (Table 5), and this effect was more pronounced under pretilachlor (37.2%), in spite of exerting lower number of phosphatesolubilizers, as compared to thiobencarb (29.9%) at lower concentrations. This indicated that pretilachlor at field application rate highly induced the efficiency of the phosphate-solubilizing microorganisms rather than their growth and multiplication (Nongthombam et al, 2008).…”
Section: Effect On Biochemical Processessupporting
confidence: 79%
“…Following the method of Das et al (2012) Microbial biomass carbon was determined by chloroform fumigation following the method of Joergensen (1995). There were two sets of moist soil-one set in conical flasks fitted with a stopper and the other set in beakers.…”
Section: Sample Collection and Analysismentioning
confidence: 99%
“…Using pesticides as nutrient and energy source (Paul et al, 2010), the higher growth and activity of P-solubilizing micro-organisms as well as greater acid and alkaline phosphatase activity affected greater solubilization of insoluble inorganic phosphate compounds as well as mineralization of organic P to a larger extent. This in turn was translated to the enhancement in P availability of soil (Das and Debnath, 2006;Das et al, 2012). Even the microbial phosphorus may provide addendum to P availability in soil after mineralization of dead zymogenous organisms (Tiessen et al, 2011).…”
Section: Total and Available Phosphorusmentioning
confidence: 99%
See 1 more Smart Citation